Efektifitas Kombinasi Ektrak Daun Pepaya (Carica Papaya L.) Dengan Ektrak Biji Pepaya (Carica Papaya L.) Terhadap Penurunan Kadar Gula Darah Pada Tikus Putih Jantan Hiperglikemik - Fitriani, Hikmah; Sanif, Edial; Nurdina , Annisa Fadhilah (Syntax Corporation, 2025)
Hyperglycemic is a medical condition when the blood glucose level increases over the normal ranges. Hyperglycemic is one of the typical symptoms of Diabetes Mellitus (DM) although it could probably happen in the different conditions. Nowadays, the studies of epidemiology show that there seems to be the increasing of incidental numbers and DM type-2 prevalence all over the world. WHO predicts the increasing of the diabetics in Indonesia will be from 8.4 million in 2000 to 21.3 million in 2030. Aim: To know the effectiveness of giving the papaya leaf and seed extract combination in reducing the blood glucose level of male wistar strain rats induced by streptozotocin. Research Method: This research used the experimental research along with “pre and post-test control group” design and 35 male wistar strain rats (Rattus norvegicus) as the research object. The rats were divided into 2 control groups (K(+) induced by glibenclamide and K(-) by distilled water) and 3 experimental groups (P1 induced by papaya leaf extract, P2 induced by papaya seed extract, P3 induced by the combination of both extracts). Research Results: Groups showing the significant reduction of blood glucose level by paired T-test were positive control groups, P1, P2, P3 with (P<0.05). The different significant reduction of blood glucose level using one way ANOVA test along with the value (p=0.000) was showed by positive control groups, P1, P2, P3. Conclusion: Giving the combination of papaya leaf and seed extract is more effective in reducing blood glucose level than the independent one.